Urology residents experience comparable workload profiles when performing live porcine nephrectomies and robotic surgery virtual reality training modules. Issue 1 (March 2016) - Mouraviev, Vladimir; Klein, Martina; Schommer, Eric; Thiel, David; Samavedi, Srinivas; Kumar, Anup; Leveillee, Raymond; Thomas, Raju; Pow-Sang, Julio; Su, Li-Ming; Mui, Engy; Smith, Roger; et al.
Abstract In pursuit of improving the quality of residents' education, the Southeastern Section of the American Urological Association (SES AUA) hosts an annual robotic training course for its residents. The workshop involves performing a robotic live porcine nephrectomy as well as virtual reality robotic training modules. The aim of this study was to evaluate workload levels of urology residents when performing a live porcine nephrectomy and the virtual reality robotic surgery training modules employed during this workshop. Twenty-one residents from 14 SES AUA programs participated in 2015. On the first-day residents were taught with didactic lectures by faculty. On the second day, trainees were divided into two groups. Half were asked to perform training modules of the Mimic da Vinci-Trainer (MdVT, Mimic Technologies, Inc., Seattle, WA, USA) for 4 h, while the other half performed nephrectomy procedures on a live porcine model using the da Vinci Si robot (Intuitive Surgical Inc., Sunnyvale, CA, USA). After the first 4 h the groups changed places for another 4-h session. All trainees were asked to complete the NASA-TLX 1-page questionnaire following both the MdVT simulation and live animal model sessions. A significant interface and TLX interaction was observed. The interface by TLX interaction was further analyzed to determine whether the scores of each of the six TLX scales varied across the two interfaces. The means of the TLX scores observed at the two interfaces were similar. The only significant difference was observed for frustration, which was significantly higher at the simulation than the animal model, t (20) = 4.12, p = 0.001. This could be due to trainees' familiarity with live anatomical structures over skill set simulations which remain a real challenge to novice surgeons. Another reason might be that the simulator provides performance metrics for specific performance traits as well as composite scores for entire exercises. Novice trainees experienced substantial mental workload while performing tasks on both the simulator and the live animal model during the robotics course. The NASA-TLX profiles demonstrated that the live animal model and the MdVT were similar in difficulty, as indicated by their comparable workload profiles.